From Planning to Prevention: Risk Management Strategies in the Pre-Opening Stage of Agrotourism - Ni Ketut Mareni; Anak Agung Istri M. Septiviari; Ni Made Sri Rukmiyati; I Dewa Ayu Rai Sumariati; I Putu Arnawa (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study aims to identify and analyse operational risks during the pre-opening phase of agrotourism destinations in Indonesia and propose effective risk management strategies. The research focuses on understanding the potential risks related to safety, cleanliness, and maintenance that may impact the visitor experience and the overall reputation of the agrotourism site. A qualitative research method was employed, involving direct observations, interviews with stakeholders, and data triangulation to ensure the validity and reliability of the findings. The results highlight several key operational risks, including accidents related to traffic, cleanliness issues such as pest control, and maintenance challenges of ageing infrastructure. These risks pose significant threats to visitors' safety and agrotourism businesses' sustainability. The study recommends implementing enhanced security measures, regular cleanliness maintenance, and a structured approach to infrastructure maintenance to minimise these risks. These strategies are expected to improve service quality, ensure safety, and enhance the competitiveness of agrotourism destinations. The findings contribute to developing a comprehensive risk management framework for agrotourism in the pre-opening phase, offering practical solutions for stakeholders in the industry.